Roadmap to Building a Cell: An Evolutionary Approach - Abil, Zhanar; Danelon, Christophe (Frontiers in Bioengineering and Biotechnology, 2020)
Laboratory synthesis of an elementary biological cell from isolated components may aid in understanding of the fundamental principles of life and will provide a platform for a range of bioengineering and medical applications. In essence, building a cell consists in the integration of cellular modules into system’s level functionalities satisfying a definition of life. To achieve this goal, we propose in this perspective to undertake a semi-rational, system’s level evolutionary approach. The strategy would require iterative cycles of genetic integration of functional modules, diversification of hereditary information, compartmentalized gene expression, selection/screening, and possibly, assistance from open-ended evolution. We explore the underlying challenges to each of these steps and discuss possible solutions toward the bottom-up construction of an artificial living cell.